Effective communication is key to intensive care nurses' willingness to provide nursing care amidst the COVID-19 pandemic. (February 2021) - Lord, Heidi; Loveday, Clare; Moxham, Lorna; Fernandez, Ritin
Abstract: Background: The COVID-19 pandemic posed and continues to pose challenges for health care systems globally, particularly to Intensive Care Units (ICU). At the forefront of the ICU are highly trained nurses with a professional obligation to care for patients with COVID-19 despite the potential to become infected. The aim of this study was to explore ICU nurses' willingness to care during the COVID-19 pandemic. Methods: A prospective cross-sectional study to explore ICU nurses' willingness to provide care during the COVID-19 pandemic was undertaken between 25 March and 3 April 2020 at a large principal and referral teaching hospital in Sydney, NSW Australia. Results: A total of 83 ICU nurses completed the survey. Approximately 60% reported receiving sufficient information from managers regarding COVID-19 and about caring for a patient with COVID-19. Ninety percent of nurses were concerned about spreading COVID-19 to their family. Sixty one percent of the nurses indicated that they were willing to care for patients with COVID-19. Receiving timely communication from managers was the only predictor of willingness to care among ICU nurses. Conclusions: Effective communication is a vital component during a public health emergency in order to promote nurses' willingness to care for patients in the ICU.